Pre-Image Variational Principle for Subadditive Sequence Functions (Communications in Mathematical Research, 2021)
In this paper we define the pre-image topological pressure for a sequence of subadditive continuous functions on the compact metric space. And we also give a subadditive pre-image variational principle under a very weak condition.
Keywords: variational principle; pre-image pressure; pre-image entropy.